Anticonvulsants and Serum Cholesterol - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The effect of antiepileptic drugs (AED) on total cholesterol, high density lipoprotein (HDL) cholesterol and triglycerides was studied in 208 epileptic children compared with 175 normal children at the University of Bologna, Italy.